The Application Of Learning Using Animated Video Applications To Improve Mathematics Learning Outcomes Of Grade VI Students Of SD Negeri 018 Rambah - Aditya Gusman Nugroho; Nauli Tama Sari (STKIP Rokania Pasir Pangaraian, 2021)
This study aims to improve the ability of class VI students of SD Negeri 018 Rambah in understanding Fraction Count Operation material in mathematics learning using Animation Video media. This research is a classroom action research consisting of 2 (two) cycles, each cycle consisting of 4 (four) ) stages. Cycles I and II each consisted of 3 meetings. The research subjects consisted of sixth grade students of SD Negeri 018 Rambah. Data on the ability of students to understand fractional arithmetic operations were collected using observation sheets and tests. Based on the results of data analysis, the average post-test score in the first cycle was 70.24 with the percentage of students achieving the Minimum Completeness Criteria (KKM) of 67% . In the second cycle, the average post-test score was 83.57 with the percentage of students who achieved the Minimum Completeness Criteria (KKM) of 86%. The results showed that the application of animated video media had an effect on increasing mathematics learning outcomes for fractional arithmetic operations.